Comparison of Superparamagnetic and Ultrasmall Superparamagnetic Iron Oxide Cell Labeling for Tracking Green Fluorescent Protein Gene Marker with Negative and Positive Contrast Magnetic Resonance Imaging - Zhuoli Zhang; Rohan Dharmakumar; Nicole Mascheri; Zhaoyang Fan; Shengyong Wu; Debiao Li (Molecular Imaging)
The objectives of this study were to investigate the feasibility of imaging green fluorescent protein (GFP)-expressing cells labeled with iron oxide nanoparticles with the fast low-angle positive contrast steady-state free precession (FLAPS) method and to compare them with the traditional negative contrast technique. The GFP-R3230Ac cell line (GFP cell) was incubated for 24 hours using 20 μg Fe/mL concentration of superparamagnetic iron oxide (SPIO) and ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles. Cell samples were prepared for iron content analysis and cell function evaluation. The labeled cells were imaged using positive contrast with FLAPS imaging, and FLAPS images were compared with negative contrast T 2 *-weighted images. The results demonstrated that SPIO and USPIO labeling of GFP cells had no effect on cell function or GFP expression. Labeled cells were successfully imaged with both positive and negative contrast magnetic resonance imaging (MRI). The labeled cells were observed as a narrow band of signal enhancement surrounding signal voids in FLAPS images and were visible as signal voids in T 2 *-weighted images. Positive contrast and negative contrast imaging were both valuable for visualizing labeled GFP cells. MRI of labeled cells with GFP expression holds potential promise for monitoring the temporal and spatial migration of gene markers and cells, thereby enhancing the understanding of cell- and gene-based therapeutic strategies.